Kemampuan Berpikir Kreatif Siswa dalam Mengajukan Masalah Kontekstual Ditinjau dari Kemampuan Matematika - Rossalia, Alya; Santoso, Tatag Yuli Eko (Universitas Negeri Surabaya, 2025)
Creativity is obtained from creative thinking activities that a person does. Creative thinking skills can be developed through mathematics education. To develop the ability to think creatively, a way is needed through activities in learning mathematics. One possible activity is through problem posing. This research employs a qualitative technique with descriptive research type. During the even semester of the 2022–2023 academic year, seventh grade students of SMP Negeri 1 Mojowarno participated in this study. Fluency, adaptability, and originality are the study's markers of creative thinking abilities. A test of arithmetic proficiency was administered first, followed by a test of problem submission, as part of the data gathering method. The study's findings indicate that pupils with strong mathematics ability tend to fulfill more thinking ability indicators than students with low mathematical ability. Math-proficient students have varying capacities for creative thought. Level 4 creative thinking ability is attained by the first student with strong arithmetic skills, who satisfies all three criteria. The second student had level 0 creative thinking ability since he did not match the three markers of creative thinking ability, while having a strong mathematical aptitude. Students with a moderate level of mathematical proficiency, however, had distinct capacities for creative thought. One of the markers of creative thinking ability, a level 1 creative thinking ability, was reached by the first subject with a modest aptitude for mathematics. He had a level 0 creative thinking capacity since the second subject, who had a modest aptitude for mathematics, did not match the three criteria.